Analysis Juridical to Protection of Computer Programs in Law Number 28 of 2014 - Anggie Sinthiya, Ida Ayu Putu (JLASA (Journal of Law and State Administration), 2025)
Computer program as results work intellectual has become element important in the digital era. Constitution Number 28 of 2014 concerning Copyright was introduced as response to development technology and needs for strengthen system protection right creation in Indonesia. The research method used in Study This is study law normative or legal research. Research law normative own focus main in analysis document law, including laws, regulations, and theories related laws​ with the Computer Program Copyright Act Number 28 of 2014 has give solid foundation​ in effort overcome computer program piracy. Law This covers various provision laws that protect creation of computer programs, among others give right exclusive to creator and prohibit duplication without permission. With give protection clear laws, regulations​ This can support and encourage climate better economy​ healthy in the sector technology especially computer programs.